Bio-Hydrogen Production Using Landfill Leachate Considering Different Photo-Fermentation Processes - Barghash, Hind; Okedu, Kenneth E.; Al Balushi, Aisha (Frontiers in Bioengineering and Biotechnology, 2021)
Recently, it has become imperative to find new sustainable and renewable sources of energy, in order to avoid dependence on non-renewable traditional energy resources. This would help to overcome the depleting of natural resources for energy production. Hydrogen gas production using biological processes is one of the most attractive solutions in this regard, due to its high energy content and ecofriendly nature. Production of hydrogen using single photo-fermentation process and landfill leachate as substrate was carried out in this paper, by utilizing batch bio-reactor and anaerobic conditions. The pH value and temperature, play an essential role in a bio-hydrogen production process. Thus, in this study, the pH values considered were 6, 6.5 and 7.2, respectively, at a controlled temperature of 37±1 ℃. This study investigated various schemes that have the possibility of producing hydrogen using; landfill leachate alone, with leachate and addition of inoculum such as sewage sludge, and with substrate such as sucrose and glucose. All experiments were conducted with and without mixing, for effective comparative study. Heat and pH pretreatment were applied in each experiment with the objectives of decreasing the activities of methane-producing bacteria and enhancing the activities of hydrogen-producing bacteria. The hydraulic retention time used in this study was 48 hours, in order to obtain optimal performance of the schemes employed. Analysis of liquid leachate was performed for each experiment, and based on the obtained results, the maximum yield of hydrogen produced was 5,754 ml H2/L, with a medium pH scale of 6.0, fermentation temperature of 37 ±1 ℃, and constant mixing speed of 100 rpm.